Supplier selection under circular economy: An integrated entropy-EDAS method - Gupta Srikant; Varshney Niharika; Ahmed Aquil; Chatterjee Prasenjit; Kadry Seifedine (Yugoslav Journal of Operations Research, 2025)
The concept of circular economy (CE) is gaining attention from businesses and government agencies as a crucial approach to combat climate change. With increasing consumer concern for environmental and social issues, there is a growing emphasis on supporting sustainable and circular supply chains. The selection of appropriate suppliers is recognized as pivotal for achieving efficiency and profitability within a circular supply chain. This study conducts a thorough literature review to identify 16 supplier selection criteria, focusing on their suitability in CE framework. Criteria weights are determined using Entropy method, while Evaluation based on Distance from Average Solution (EDAS) method has been applied to identify the most suitable supplier. The results identified "Financial capability," "The technology required to supplement reverse logistics," and "Re-Use, Re-Manufacturing, Refurbishment" as the most predominant criteria. "Financial capability" drives circular investment, enhancing resource efficiency. "Technology for reverse logistics" optimizes material flow, reducing resource depletion. Practices like "Re-Use, Re-Manufacturing, Refurbishment" extend product lifecycles, curbing environmental impact. Using the EDAS method, Supplier 5 emerges as the top choice, reinforcing sustainable supply chain decisions. This promotes CE principles and aligns sustainable development goals, aiding managers in policy-making and prioritizing supplier criteria.